Opinion 2410: Cicindela varians Gory, 1833 (currently Cenothyla varians; Insecta, Coleoptera, Carabidae): conservation by the suppression of Cicindela varians Ljungh, 1799 approved - ICZN (Bulletin of Zoological Nomenclature, 2018)
The International Commission on Zoological Nomenclature has used its plenary power to conserve the specific name of Cicindela varians Gory, 1833 by suppressing its primary senior homonym Cicindela varians Ljungh, 1799.
Keywords: Carabidae; Cenothyla varians; Nomenclature; taxonomy; tiger beetles